1987
DOI: 10.1149/1.2100517
|View full text |Cite
|
Sign up to set email alerts
|

Problems Associated with the Electrochemical Reduction of Metal Ions in LiNO3 ‐  KNO 3 and LiClO4 ‐ KClO4 Melts: The Reduction of Nitrato and Perchlorato Complexes

Abstract: Electrochemical studies of Ag § T1 § Cd + § Pb + § Zn ++, and In +++ metal ions on platinum electrodes in molten LiNO3-KNO3 show that only silver ions are readily reduced to the metal within the electrostability region of the melt. The other metal ions form nitrato complexes that are reduced directly to the metal oxide at potentials less negative than solvent reduction. For divalent metal ions, these reactions can be represented by (MONO2) + + 2e----, MO § NO2 . Scission of the O--N bond likely occurs in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…15 The LiNO 3 −KNO 3 showed wider electrochemical window at the lower operating temperature than the halides. 44 However, the LiNO 3 −KNO 3 generates exothermic reactions with the Li alloy negative electrodes, which lead to fire disasters. 15 The Li[Tf 2 N] mixtures have wide electrochemical windows of over 5.0 V due to the high oxidation resistance of the Tf 2 N − .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…15 The LiNO 3 −KNO 3 showed wider electrochemical window at the lower operating temperature than the halides. 44 However, the LiNO 3 −KNO 3 generates exothermic reactions with the Li alloy negative electrodes, which lead to fire disasters. 15 The Li[Tf 2 N] mixtures have wide electrochemical windows of over 5.0 V due to the high oxidation resistance of the Tf 2 N − .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Anodic dissolution of the CuO deposit would be expected to occur by the reaction with either nitrate CuO + ONO~ -~ Cu(ONO~) § + 112 O~ + 2e- [4] or residual nitrite ion…”
Section: Table I Coulombs Of Charge For Copper Aqueous Deposition (Qd)mentioning
confidence: 99%
“…ble, and the latter is converted quantitatively to superoxide in the presence of oxygen via O~ +O2=20~ [3] This picture is supported by extensive electrochemical data, 7-n electron paramagnetic resonance detection of superoxide, 12 independent manometric measurements of the oxygen uptake associated with reaction 3 above, ~3 and good correlations with similar solid-state data. TM Zambonin '5 also showed that water quantitatively converts superoxide to hydroxide (OH-) within a few hours 2 02 + H20 = 3/2 02 + 2 OH- [4] This, of course, introduces additional electrochemical reactions that would have to be taken into account in wet melts.…”
Section: Electrodeposition Of Mixedmentioning
confidence: 99%
“…Moisture present in the melt was estimated quantitatively by applying the Randles and Sevick equation [13] as Ip = (4.64 × 10 6 /T 1/2 ) n 3/2 AD ½ Cv ½ ( 2 ) The moisture content was found on the order of around 10 -4 M present at 300 0 C. A different explanation has been proposed for interaction of water reduction reaction with nitrate ion reduction. However, complex ion formation [ 14,15] involving water and nitrate ions is the most acceptable one. This can be presented in following steps…”
mentioning
confidence: 99%